Surgical treatment of mandibular fracture resulting from first molar extraction: case report (Research, Society and Development, 2021)
Extraction is one of the most common procedures performed by dental surgeons in their daily clinical practice. Among the trans and postoperative complications associated with this procedure can be mentioned the occurrence of trismus, infections, edema, alveolitis, paresthesia or fractures. The purpose of this study was to report a clinical case of a mandibular fracture associated with first molar extraction, approaching its main risk factors and treatment. Patient JSS, 24 years old, female, was referred to the service of Maxillofacial Surgery due to complications resulted from the extraction of element 36. On physical examination, was observed the presence of fragment mobility, communication of bone tissue with the oral environment and pain complaint was reported by the patient. Computed tomography showed the presence of a fracture in the region of the mandibular body on the left side. The planned surgical proposal was the intraoral debridement of bone fragments, extraoral access in the base of the mandible, fixation of the fracture with plate 2.4 and intraoral and extraoral access suture. During the surgical procedure, it is of great importance that the dental surgeon be aware to the signals emitted by the patient, such as clicks associated with severe pain, profuse bleeding or crackling as these symptoms may be the result of mandibular fracture. When any of these signs are found during the operation, the professional must investigate the occurrence of a possible fracture. It is concluded that in addition to performing a good preoperative evaluation, the dental surgeon must carry out a correct planning of the surgical act based on the basic principles of the surgical technique.